SOSIALISASI PENCEGAHAN PERKAWINAN ANAK SEBAGAI UPAYA MENINGKATKAN KESADARAN DAN PENGETAHUAN AKAN DAMPAK PERKAWINAN DIBAWAH UMUR DI YAYASAN PONDOK PESANTREN ASH SHAMADI NW TANAK MAIK - Lilhamdi, M Riki; Nurrizka, Siti; Siska Yunita, Eliza; Wahyuni, Sri; Maryati Ningsih, Resthi; Utami, Sulastri; Ananda, Selly; Oktapian, Tomi; Arjuna Surya Dharma Putra, I Made; Zuldiansyah, Gusti; Al Sasongko, Sudi Mariyanto (Jurnal Wicara, 2025)
Child marriage is a serious issue that has a negative impact on children's health, education and welfare. The aim of this activity is to explore the prevention of child marriage at the Ash Shamadi NW Tanak Maik Islamic Boarding School Foundation as an effort to increase public awareness and knowledge regarding the impact of underage marriage. Through an outreach program involving students from the Ash Shamadi NW Tanak Maik Islamic Boarding School Foundation, it is hoped that it can increase understanding of the dangers and consequences of child marriage. This activity was carried out using a qualitative approach through interviews and observations. The results of the activity showed that the outreach was successful in increasing participants' awareness of the importance of postponing marriage and the need to protect children's rights. The method used in this socialization activity is by presenting material, interactive discussions, and counseling about the consequences of health, education, and children's rights. Socialization participants experienced increased knowledge regarding the dangers of child marriage, with most participants revealing that they previously did not understand the psychological and social impacts of marriage at an early age. This program was also successful in increasing participants' commitment to supporting the movement to prevent child marriage in Islamic boarding schools and the community. It is hoped that this outreach activity can be expanded to involve more parties, including families and the government, in order to create greater social change regarding the issue of child marriage.